Moisture sorption isotherms and hysteresis of soybean grains - Juliana Soares Zeymer (Acta Scientiarum. Agronomy, 2023)
Knowledge of the relationship between the equilibrium moisture content of the product and the air that involves it is essential to guarantee product quality and preserve its characteristics during storage. This trend can be studied by sorption isotherms. Thus, this study aimed to obtain desorption and adsorption isotherms of soybean grains to determine the mathematical model that best fits the experimental data and analyze the hysteresis phenomenon. Soybean grains with a moisture content of 21.95% (db) were used to verify the desorption process. The grains were dried until 3.50% (db) for the adsorption process. The static-gravimetric method was employed to determine the equilibrium moisture content of the grain at different temperatures (10, 20, 30, 40, and 50°C) and relative humidity levels (0.10 to 0.92%). Eight mathematical models were fitted to the experimental data. The modified Halsey model satisfactorily represented the desorption and adsorption phenomena of soybean grains. The equilibrium moisture content of soybean grains increased along with an increment in water activity. The increase in temperature led to a reduction in the equilibrium moisture content of soybean grains at a constant water activity. The equilibrium moisture content values obtained by desorption are higher than those obtained by adsorption, indicating the hysteresis phenomenon at the studied temperature range. The isotherms obtained for the desorption and adsorption process were classified as type III because of the high oil content in soybean grains.